Delayed neurological maturation is a cause for distress during fetal growth restriction - I. V. Lakhno; S. E. Malikova (Publishing House TRILIST, 2020)
Theory of fetal programming contributes to a better understanding of the relationship of many human diseases with antenatal period pathology. Regulatory impact of nervous system is of great importance. Fetal growth restriction (FGR) is a convenient model for investigation of the abnormalities of fetal neurodevelopment. Fetal heart rate variability is a well-known approach for fetal autonomic function detection. The aim of the study was to detect several patterns of autonomic nervous regulation in FGR complicated by fetal distress or without fetal distress. Materials and methods. Totally 64 patients at 26-28 weeks of gestation were enrolled. 23 patients had normal fetal growth and were included in the Group I (control). 20 pregnant women with FGR without fetal distress were observed in Group II. 21 patients with FGR and fetal distress were included in Group III. Fetal heart rate variability and conventional cardiotocographic patterns were obtained from the RR-interval time series registered from the maternal abdominal wall via non-invasive fetal electrocardiography. Results. Suppression of the total level of heart rate variability with sympathetic overactivity was found in FGR. The maximal growth of sympathovagal balance was found in Group III. Fetal deterioration was associated with an increased quantity of decelerations, reduced level of accelerations, and decreased of short term variations and low term variations. But a decelerative pattern before 26 weeks of gestation was normal. Therefore fetal autonomic malfunction could be a result of persistent neurological immaturity in FGR. The approach based on the monitoring of fetal autonomic maturity in the diagnosing of its well-being should be tested in further studies. Conclusion. Fetal heart rate variability variables and beat-to-beat variations parameters could be the sensitive markers of neurological maturation and good predictors for fetal deterioration.